Sosialisasi Peran Orangtua dan Satuan PAUD Dalam Menciptakan Transisi PAUD SD Yang Menyenangkan - Setyowati, Rina Insani; Shofwan, Arif Muzayin; Farantika, Dessy; Istikomah, Istikomah (Abdimas Indonesian Journal, 2025)
Children’s school readiness is a critical factor in determining their future academic and social success. The transition from Early Childhood Education (ECE) to primary school often presents a significant challenge for young learners. At this stage, the role of parents and ECE institutions becomes crucial in ensuring children are adequately prepared to navigate this shift. Failure to achieve a smooth transition can result in anxiety, discomfort, and difficulties adapting to the new school environment. Therefore, special attention must be given to support children’s readiness for entering the next level of education. Purpose of the Study: The primary objective of strengthening the involvement of parents and ECE units in preparing children for school is to foster a positive and low-stress transition from early education to primary education. Methods: This initiative was carried out on September 12, 2024, using a combination of interactive dialogue, lectures, group discussions, and Q&A sessions. Results: Through awareness-building efforts directed at parents and ECE educators, children’s readiness for school can be enhanced by stimulating essential social, emotional, and academic competencies required in a primary school setting. (5) Conclusions: By conducting outreach to parents and teachers at Al Hidayah Kindergarten Sanankulon, this program aimed to facilitate a joyful and confident transition to primary school. As a result, children are expected to enter elementary school with a stronger sense of self-confidence and enthusiasm for learning.